Lack of PI 3-kinase isoform p110alpha impairs SMC differentiation and proliferation and promotes aortic aneurysm formation. (3rd October 2022) - Vantler, M; Schorscher, M; Moore, J B; Berhausen, E M; Zierden, M; Mollenhauer, M; Adam, M; Mehrkens, D; Baldus, S; Rosenkranz, S
Abstract: Background: Proliferation and phenotypic modulation of vascular smooth muscle cells (SMCs) significantly contribute to the functionality of the aortic wall. Dysregulation of underlying signal transduction pathways impairs the vessel wall structure and promote the development and progression of abdominal aortic aneurysms (AAA). The PI 3-kinase (PI3K) isoform p110α is activated downstream of receptor tyrosine kinases (RTKs) and represents the most relevant PI3K isoform in SMCs. Aim: This project follows the hypothesis that p110α deficiency impairs proliferation and phenotypic modulation of SMCs as well as the structure of the extracellular matrix (ECM) and therefore promotes the development and progression of AAA. It was investigated how p110α deficiency affects the plasticity of SMCs, the production and structure of ECM components, and the formation of AAA. Methods and results: Western blot analyses showed that SMCs isolated from smooth muscle specific p110α−/− (sm-p110α−/−) mice were characterized by decreased expression of the differentiation markers sm-α-actin, calponin and sm-MHC. Mechanistically, phosphorylation of key modulators of the SMC phenotype – AKT1, AKT2, FOXO1, -3 and -4 as well as GSK3β – was impaired in p110α−/− SMCs after RTK stimulation. These findings indicate that phenotypic modulation of p110α−/− SMCs is restricted. In addition, protein expression of elastin and fibrillin was reduced in p110α−/− SMCs. In silico analysis (MatLab macro CT-FIRE and Curvalign) of the ECM produced by SMCs in vitro revealed a significantly reduced elastin fiber length and width in p110α−/− SMCs compared to fibers produced by WT SMCs (p<0.05). Consistently, aortas from sm-p110α−/− mice showed a significantly higher number of elastic fiber breaks specifically in the thoracic section than WT controls (289±31 mmm –2 versus 190±9 mmm –2, n=5, p=0.015). Aortic aneurysms in sm-p110α−/− mice and wild-type littermates were analyzed using the established porcine pancreatic elastase (PPE) model. PPE was perfused into the infrarenal aorta to induce AAA formation. Ultrasound examination of the aorta revealed an enlarged aortic diameter in all PPE-treated mice. However, the increase in aortic diameter in sm-p110α−/− mice (70.16±10.82% mm, n=9) was significant more pronounced compared to wild-type animals (42.44±5.99%, n=10) (p<0.05). Three days after PPE perfusion, the number of elastic fiber breaks was significantly increased, and amount of proliferating SMCs were decreased in the infrarenal aorta of sm-p110α−/− mice compared to WT controls. Conclusion: p110α deficiency in SMCs impairs aortic wall structure and promotes the development and progression of aortic aneurysms. Mechanistically, p110α activity maintains a differentiated SMC phenotype as well as the expression and assembly of ECM components. These data identify p110α signaling as a modifiable target for preventive and therapeutic strategies for aortic aneurysms. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Deutsche Forschungsgemeinschaft